2010
DOI: 10.2165/11539320-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and Disposition of Tribendimidine and Its Metabolites in Healthy Chinese Volunteers

Abstract: Background: Tribendimidine is a new anthelmintic agent synthesized by Chinese scientists. It is a broad spectrum agent with high activity against parasites. However, its disposition and metabolism remain unknown.Objective: To investigate the metabolism, disposition, and metabolites of tribendimidine in healthy human volunteers.Methods: Twelve healthy Chinese volunteers were chosen after clinical assessment of health status and laboratory tests. They received single oral doses of tribendimidine 400mg enteric-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 4 publications
2
31
2
Order By: Relevance
“…2 The ED 1 -ED 95 curve of tribendimidine (TBD) and its metabolites and dADT in treatment of rats infected with Nippostrongylus braziliensis aforementioned that AdADT has been degraded in the stomach of the rat before the drug reaches to the small intestine. According to the pharmacokinetic data of TBD, dADT is a major metabolite present in the blood and urine after oral administration of TBD, while the secondary metabolite of AdADT is found in the urine (Yuan et al 2008b). Therefore, it is suggested that in treatment of intestinal nematodes, TBD and dADT display the major role, and in treatment of C. sinensis, dADT is the major effective metabolites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 The ED 1 -ED 95 curve of tribendimidine (TBD) and its metabolites and dADT in treatment of rats infected with Nippostrongylus braziliensis aforementioned that AdADT has been degraded in the stomach of the rat before the drug reaches to the small intestine. According to the pharmacokinetic data of TBD, dADT is a major metabolite present in the blood and urine after oral administration of TBD, while the secondary metabolite of AdADT is found in the urine (Yuan et al 2008b). Therefore, it is suggested that in treatment of intestinal nematodes, TBD and dADT display the major role, and in treatment of C. sinensis, dADT is the major effective metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…In a clinical trial undertaken in 1980, the results showed that amidantel possessed higher efficacy against A. lumbricoides and Ancylostoma duodenale infection in humans, but none of the patients with N. americanus was cured by the drug (Rim et al 1980). Apart from plasma, dADT was also found in urine by high-performance liquid chromatography method (Yuan et al 2008b). Interestingly, dADT may proceed the secondary metabolism which results in formation of acetylated dADT (AdADT) detected in urine (Yuan et al 2008b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, dADT is further metabolized to AdADT ( Fig. 1d; Yuan et al 2008b) and its chemical structure is similar to that of ADT. Since adult C. sinensis parasitize in the liver bile duct system, the oral drug displays its effect against the worms only after it is absorbed from the intestinal tract.…”
Section: Discussionmentioning
confidence: 97%
“…1c; Tomlinson et al 1985;Yuan et al 2008a) and its secondary metabolite, acetylated dADT (AdADT; Fig. 1d), were detected in the urine (Yuan et al 2008b). Although the predict metabolite, terephthaldehyde (TPAL; Fig.…”
Section: Introductionmentioning
confidence: 93%